Molecular-field Molecular-field Study on Sn Substituted Yttrium Iron Garnet - Duong, Nguyen (VNU Journal of Science: Mathematics - Physics, 2018)
Samples with the compositions Y 2.9 Ca 0.1 Fe 4.9 Sn 0.1 O 12 and Y 3 Fe 4.9 Sn 0.1 O 12 were prepared by using a sol-gel technique. The influence of the substituted non-magnetic cations with different valences in the structural and magnetic properties was studied. X-ray diffraction and field-emission electron scanning microscope techniques were used to study the crystal structure and morphology. Magnetization curves in fields up to 10 kOe and in temperature range from 80 K to 570 K were measured by means of a vibrating sample magnetometer. Saturation magnetization as a function of temperature of the two samples was analyzed based on the molecular-field theory from that models for site occupancy and valence states of cations in the crystal structures were derived.